Society and the State: The Movement to Protect the Living Space of Indigenous People on Bengkalis Island - Hasanuddin Hasanuddin; Evawani Elysa Lubis; Mashur Fadli; Khairul Amri; Agus Alfan (Jurnal Ilmu Sosial dan Humaniora, 2024)
This research aims to analyze community movements and efforts made by the state to protect the living space (territory) of indigenous peoples on Bengkalis Island. For generations, indigenous people have used the mangrove forest area as a living space. On the way, the indigenous people found that their living space was damaged and narrowed, which they understood but were unable to control. This research is qualitative, obtaining data through observation, interviews, and aggregate data. The research data is then analyzed following a logical flow built and adjusted to the flow of field research data. The resource mobilization theory was used as a guide. This research found that facing the rate of mangrove destruction as a living space, indigenous tribes can only adapt slowly by utilizing the remaining open resources and opportunities. The community movement to protect mangrove forests as a living space for indigenous people on Bengkalis Island is still limited to being carried out by the indigenous people. The new movement is only in the form of building relationships with officials who have power in the region, hoping that indigenous people can carry out their traditional activities, namely utilizing mangrove forests as their living space. This movement is far from successful. In the form of the Regional Environmental Protection and Management Policy, local government policy keeps indigenous people away from mangrove forests as their living space.